Beginning ASP.NET E-Commerce in CSharp - Darie, Cristian (Apress, 2012)
Welcome to Beginning ASP.NET E-Commerce in C#: From Novice to Professional! This book is a practical, step-by-step ASP.NET and SQL Server tutorial that teaches you real-world development practices. Guiding you through every step of the design and build process, this tutorial will teach you how to create high-quality, full-featured, extensible e-commerce web sites. Over the course of the book, you will develop the necessary skills to get your business up on the Web and available to a worldwide audience. In each chapter, you will implement and test new features of your e-commerce web site, and you will learn the theoretical foundations required to understand the implementation details. The features are presented in increasing complexity as you advance throughout the book, so that your journey will be as pleasant and painless as possible. By the end of the book, you’ll understand the concepts and have the knowledge to create your own powerful web sites.